Genetic and environmental determinants of dental occlusal variation in South Australian twins - Townsend Grant C.; Corruccini Robert S.; Richards Lindsay C.; Brown Tasman (Sciendo, 1998)
As part of an ongoing study of dentofacial morphology in South Australian twins, several occlusal traits were compared between forty eight monozygous and thirty four dizygous twin pairs, as well as estimating genetic variances for these features. Significant genetic variance was noted for incisal overbite and overjet, sagittal molar relationship, and also rotations and displacements of anterior teeth. However, heritability estimates were low in magnitude (about 30%) emphasising the importance of environmental influences on occlusal variation.